Augmented expression of secondary lymphoid tissue chemokine and EBI1 ligand chemokine in Crohn's disease. Issue 10 (27th September 2005) - Kawashima, D; Oshitani, N; Jinno, Y; Watanabe, K; Nakamura, S; Higuchi, K; Arakawa, T
Abstract : Background: A dominant T helper type 1 (Th1) immune response is thought to be involved in Crohn's disease (CD). SLC/CCL21 and ELC/CCL19, chemokines that regulate T cell homing and promote recirculating T and dendritic cell (DC) interactions, help control antigen specific T cell responses. Aims: To investigate the Th1 response and SLC and ELC in CD pathogenesis. Methods: Surgically resected intestine and mesenteric lymph nodes (MLNs) from controls and patients with CD and ulcerative colitis (UC) were investigated. CD3, CD83, HECA452, VEGFR3, SLC, ELC, and CCR7 expression was studied immunohistochemically. CCR7 mRNA was quantified using real time RT-PCR. Results: ELC was almost undetectable in intestinal samples. SLC was found sporadically in lymphoid follicles, lymphoid aggregate venules, and lymphatic vessels. In MLNs, SLC was highly expressed in high endothelial venules (HEVs), lymphatic vessels, and stromal DCs, predominantly in T cell areas. ELC was highly expressed in mature DCs. There were significantly more SLC positive HEVs and ELC positive mature DCs, important components of T cell areas, in CD. SLC, ELC, and CCR7 mRNA was significantly higher in CD MLNs compared with UC. CD MLNs had increased expression of SLC and ELC, mainly in HEVs, mature DCs, and lymphatic vessels, inducing T cell hyperplasia. CCR7 mRNA was increased in T cell areas. Conclusion: The dominant Th1 immune response is facilitated by interaction of SLC positive HEVs/lymphatic vessels, ELC positive mature DCs, and CCR7 positive T cells in hyperplastic T cell areas. In CD, memory T cells and mature DCs may home to MLN.